Islamic Perspective on Women Empowerment: The Role of Tafarkin Tsira Islamic Center Azare, Bauchi State, Nigeria - Muhammad, Adamu Abubakar; Ardo, Adam Muhammad; Idriss, Ibrahim Dahiru (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2024)
This study explores the Islamic perspective on women's empowerment and the critical role of Tafarkin Tsira Islamic Center Azare in promoting women's empowerment for a more inclusive and equitable society. This study adopts the literature study method with a systematic and comprehensive approach to literature analysis in the search, collection, and evaluation of literature sources relevant to the topic of study, as well as a semi-structured interview with pertinent people. The results of the study stated that Islam recognizes education and empowerment for both men and women as means of livelihood and religious practice. By providing equal access to Islamic, western, and vocational education, people can develop the necessary skills for knowledge sharing and business practice to play an active societal role. However, significant challenges need to be addressed, such as limited access to funds, gender bias within societies, social norms, and security challenges. The center is always trying to support the general community on such issues, especially gender equality and women's empowerment for the betterment of society. It is recommended that with the shared commitment of governments at all levels, educational institutions, community leaders, religious scholars, and families, women's empowerment can be a driven force that encourages women's participation in businesses, vocational pursuits, and creativity to create a more just, inclusive, and sustainable society, as well as strengthening the role of women in society and overcoming the barriers that prevent women from reaching their full potential and contribution to their quarter.